Draft Five-Year Plan and Draft Tribal Sub-Plan 1978-83 Himachal Pradesh Scheme-Level and Major-Head Formats - Planning Commission (Planning Commission, 1978)
Cost Plan Outlay and Expenditure Rs in lacs Medical and Health Tribal Area Sub-Plan Employment Major Hear(Format) Non Plan Expenditure.
Planning Department, Himachal Pradesh Government